COMMUNITY PARTICIPATION IN THE IMPLEMENTATION OF WASTE MANAGEMENT POLICIES IN MEDAN SUNGGAL DISTRICT, PINANG BARIS - Desi Marlina Sidabutar; Faiz Muhammad Zacky; Juni Kristiani Meliala; Peter Patiangbanua Purba; Suci Rohani br Panjaitan; Julia Ivanna (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
This study aims to determine community participation and identify obstacles in the implementation of waste management policies in Medan Sunggal District, specifically the Pinang Baris area. This study uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Informants in this study consisted of local residents and Medan City Environmental Agency employees who were deemed to have relevant information related to the issues being studied. The data obtained were then analyzed inductively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that community participation in the implementation of waste management policies is still relatively low and inconsistent. This is evident in the community's irregular involvement in community-based activities, suboptimal household waste management practices, and low awareness of maintaining environmental cleanliness. Furthermore, the community still tends to mix waste and has not implemented sustainable waste sorting. This situation indicates that public awareness is actually starting to develop, but has not yet been matched by strong habits and commitment in daily practice. Furthermore, this study found several obstacles to the implementation of waste management policies, namely low public awareness, limited supporting facilities such as adequate trash bins, indiscriminate waste disposal, and a lack of public awareness campaigns. Therefore, the successful implementation of waste management policies depends not only on public participation but also requires adequate facilities and a sustained increase in the intensity of education and outreach from the government.